2017
DOI: 10.1103/physrevc.95.065502
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence of 2p-2h meson-exchange currents

Abstract: We analyze the density dependence of the contribution of meson-exchange currents to the lepton-nucleus inclusive cross section in the two-particle two-hole channel. The model is based on the relativistic Fermi gas, where each nucleus is characterized by its Fermi momentum k F . We find that the 2p-2h nuclear response functions at their peaks scale as Ak

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
(59 reference statements)
8
28
0
Order By: Relevance
“…This is clearly observed in the right panel where it is shown that all data overlap within their error bars. This result confirms our previous study in [51], where we predicted that 2p2h response scales as k 3 F . It is important to point out that the minimum in the cross section shown in Fig.…”
supporting
confidence: 93%
“…This is clearly observed in the right panel where it is shown that all data overlap within their error bars. This result confirms our previous study in [51], where we predicted that 2p2h response scales as k 3 F . It is important to point out that the minimum in the cross section shown in Fig.…”
supporting
confidence: 93%
“…We used the parallel version of Flexible Atomic Code 3 (FAC v1.1.5) (Gu 2008) to compute the electronic structures of Fe XVII-XVI ions. We evaluated DR, DE, and RE with extended sets of configurations, full-order configuration mixing, and Breit interaction (Amaro et al 2017;Shah et al 2018). For DC channels of both DR and RE, we included 2s 2 2p 5 nln l and 2s2p 6 nln l configurations.…”
Section: Theorymentioning
confidence: 99%
“…Thus, the SuSAv2-MEC approach [2,3,4] is applied to the analysis of data from ν oscillation experiments with the aim of shedding light on the systematics arising from nuclear effects in both initial and final states. For practical purposes, the SuSAv2 model and the 2p-2h MEC contributions can be described in a simple way for different kinematics and nuclei [5,6,7,8,9], translating sophisticated and demanding microscopic calculations into a relatively straightforward formalism hence easing its implementation in event generators. In Fig.…”
mentioning
confidence: 99%